Structural and Functional Insights into Small, Glutamine-Rich, Tetratricopeptide Repeat Protein Alpha - Roberts, Joanna D.; Thapaliya, Arjun; Martínez-Lumbreras, Santiago; Krysztofinska, Ewelina M.; Isaacson, Rivka L. (Frontiers in Molecular Biosciences, 2015)
SGTA is a co-chaperone that interacts with molecular chaperones and steroid receptor complexes and plays an important role in various cellular pathways. It consists of three structural domains with individual functions, an N-terminal dimerisation domain (SGTA_NT) that assists protein sorting pathways, a central tetratricopeptide repeat (TPR) domain that interacts with heat-shock proteins and a C-terminal glutamine rich region that binds hydrophobic substrates. A range of biophysical techniques has been employed to characterize its structure and to investigate its interactions with binding partners. SGTA interacts with the androgen receptor and other steroid receptor complexes and has been shown to be linked to hormonally induced disease states. Therefore, a full structure of SGTA and further investigation of its function as a molecular co-chaperone could provide us with useful insights into the mechanisms of related pathologies. This review describes how some structural features of SGTA have been elucidated, and what this has uncovered about its function as a co-chaperone. A brief background on the structure and function of SGTA is given, highlighting its importance to biomedicine and related fields. The current level of knowledge and what remains to be understood about the structure and function of SGTA is summarised, discussing the potential direction of future research.